Carotid Intima-Media Thickness in Children with Chronic Kidney Disease as an Early Predictor of Cardiovascular Diseases - Zahid Hussain, Irshad Bajeer, Sabeeta Khatri, Shaziamohsin, Pawan Kumar, Seema Hashmi (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: Cardiovascular problems are very common in children with chronic kidney disease (CKD). To examine early cardiovascular risk factors, notably carotid intima-media thickness (CIMT) and pulse wave velocity (PWV). Material and Method: Case-control study was conducted in the Department of Pediatric Nephrology Sindh Institute of Urology and Transplantation Karachi from 1stFebruary 2023 to 31st July 2023. Forty two children were enrolled. CIMT and PWV were measured using ultrasonography and pulse wave analysis respectively. The following clinical parameters were also assessed: blood pressure, age, gender, etiology, duration of chronic kidney disease (CKD), estimated glomerular filtration rate (eGFR), serum albumin, calcium-phosphate product, and intact parathyroid hormone (PTH), and vitamin D levels. Results: The average age was 10.2±3.6 years, with a higher proportion of boys in the cases group (69% versus 47.6%, p-value 0.04). Most patients had normal blood pressure (78.6%), and congenital anomalies were the most common CKD etiology (57.1%). Median eGFR was 30.5 ml/min/1.73 m2, with stages 3 and 4 CKD most prevalent. Serum albumin was normal (mean 4.45±0.68), but some cases had a high calcium-phosphate product (7%) and low vitamin D levels (52%). CIMT and PWV did not differ significantly between cases and controls. Echocardiography revealed mild cardiac abnormalities in some cases. Practical implication: Some patients showed minor left ventricular expansion, while others had mildly depressed GLS and decreased LVEF. Further research should focus on longitudinal studies and explore new biomarkers for early cardiovascular risk detection. Conclusion: The various clinical characteristics such as blood pressure, mineral and bone diseases, and cardiac abnormalities are common in children with chronic kidney diseases. There were no significant changes in carotid intima-media thickness and pulse wave velocity between the cases and controls. Keywords: Chronic kidney disease, Carotid intima-media thickness, Cardiovascular disease, Pulse wave velocity